Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/sj.bjc.6601319
|View full text |Cite
|
Sign up to set email alerts
|

Second primary malignancies in thyroid cancer patients

Abstract: The late health effects associated with radioiodine ( 131 I) given as treatment for thyroid cancer are difficult to assess since the number of thyroid cancer patients treated at each centre is limited. The risk of second primary malignancies (SPMs) was evaluated in a European cohort of thyroid cancer patients. A common database was obtained by pooling the 2-year survivors of the three major Swedish, Italian, and French cohorts of papillary and follicular thyroid cancer patients. A time-dependent analysis using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
422
2
27

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(474 citation statements)
references
References 26 publications
15
422
2
27
Order By: Relevance
“…If radioiodine is being considered, prior external beam radiotherapy and concomitant glucocorticoid therapy are strongly recommended to minimize the effects of a potential TSH-induced increase in tumor size and the subsequent inflammatory effects of the radioiodine (261)-Recommendation C Management of complications of radioiodine therapy. While radioiodine appears to be a reasonably safe therapy, it is associated with a cumulative dose-related low risk of early and late onset complications such as salivary gland damage, nasolacrimal duct obstruction (268), and secondary malignancies (267). Therefore, it is important to ensure that the benefits of repeated radioiodine therapy outweigh the potential risks.…”
Section: Differentiated Thyroid Cancer: Management Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…If radioiodine is being considered, prior external beam radiotherapy and concomitant glucocorticoid therapy are strongly recommended to minimize the effects of a potential TSH-induced increase in tumor size and the subsequent inflammatory effects of the radioiodine (261)-Recommendation C Management of complications of radioiodine therapy. While radioiodine appears to be a reasonably safe therapy, it is associated with a cumulative dose-related low risk of early and late onset complications such as salivary gland damage, nasolacrimal duct obstruction (268), and secondary malignancies (267). Therefore, it is important to ensure that the benefits of repeated radioiodine therapy outweigh the potential risks.…”
Section: Differentiated Thyroid Cancer: Management Guidelinesmentioning
confidence: 99%
“…Surgical correction should be considered for nasolacrimal outflow obstruction, which often presents as excessive tearing (epiphora) but also predisposes to infectionRecommendation B Second malignancies and leukemia from radioiodine therapy. Long-term follow-up studies demonstrate a very low risk of secondary malignancies (bone and soft tissue malignancies, colorectal cancer, salivary tumors, and leukemia) in long-term survivors (267). The risk of secondary malignancies is dose-related (267).…”
Section: Differentiated Thyroid Cancer: Management Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, several other cancer sites showed significantly increased risks in both directions, including salivary glands, prostate, breast, kidney, scrotum, brain and leukemia. A relationship between the total dose of I 131 and SPT has been reported for solid cancers and leukemias [5]. Verkooijen et al differ to suggest that this phenomenon occurs only due to genetic predisposition and environmental factors, as at least half of breast cancers occur before the treatment with I 131 for thyroid cancer [6].…”
Section: Discussionmentioning
confidence: 99%
“…In a series of articles in the 1950s by Seidlin, the father of radioiodine treatment for thyroid carcinoma, and coworkers [31][32][33] it was well documented that there is an excess risk of leukaemia after treatment with high cumulative activities of radioiodine [34,35], correlating with the administered total radioiodine activity [36]. In practice this means that this excess risk only materializes in patients with metastatic disease after repeated (high-activity) treatments.…”
mentioning
confidence: 99%